Formation of white etching cracks at manganese sulfide (MnS) inclusions in bearing steel due to hammering impact loading. Issue 10 (18th January 2016) - Bruce, T.; Long, H.; Slatter, T.; Dwyer‐Joyce, R.S.
Abstract: Wind turbine gearbox bearings (WTGBs) are failing prematurely, leading to increased operational costs of wind energy. Bearing failure by white structure flaking (WSF) and axial cracking may both be caused by the propagation of white etching cracks (WECs) and have been observed to cause premature failures; however, their damage mechanism is currently not well understood. Crack initiation has been found to occur at subsurface material defects in bearing steel, which may develop into WECs. One hypothesis for WEC formation at these defects, such as non‐metallic inclusions, is that repetitive impact loading of a rolling element on a bearing raceway, due to torque reversals and transient loading during operation, leads to high numbers of stress‐concentrating load cycles at defects that exceed the material yield strength. In this study, a number of tests were carried out using a reciprocating hammer‐type impact rig. Tests were designed to induce subsurface yielding at stress concentrating manganese sulfide (MnS) inclusions. The effects of increasing surface contact stress and number of impact cycles, with and without surface traction, were investigated. Damage adjacent to MnS inclusions, similar to that observed in a failed WTGB raceway, was recreated on bearing steel test specimens. It has been found that increasing the subsurface equivalent stresses and the number of impact cycles both led to increased damage levels. Damage was observed at subsurface equivalent stresses of above 2.48 GPa after at least 50, 000 impact cycles. WECs were recreated during tests that applied surface traction for 1, 000, 000 impacts. Copyright © 2016 John Wiley & Sons, Ltd.